The Impact of Virtual Reality (VR) Technology on Enhancing Customer Engagement in the Online Travel Industry - Fransisco, Tio Acho (IHSA Institute, 2024)
This research investigates the impact of Virtual Reality (VR) technology on customer engagement within the online travel business. With the rapid advancements in VR, this study explores how immersive and interactive VR experiences influence customer behavior and decision-making in the travel industry. Using a mixed-methods approach, including surveys, interviews, case studies, and experiments, the research evaluates the effectiveness of VR compared to traditional engagement methods. The findings reveal that VR significantly enhances customer engagement by providing a higher level of immersion and interactivity. Participants who interacted with VR content reported increased emotional connection and longer engagement compared to those exposed to static content and traditional multimedia. Empirical data also demonstrates that VR experiences lead to higher booking rates and conversion metrics, as users are more likely to complete bookings after engaging with VR previews of destinations and accommodations. The study highlights the growing importance of personalization in VR experiences, with advancements allowing for more tailored and customized virtual tours.